Інноваційні технології викладання іноземних мов в умовах інтернаціоналізації освітнього простору - Оксана Заболотна (Pavlo Tychyna Uman State Pedagogical University, 2015)
У статті висвітлено особливості впровадження інноваційних технологій викладання іноземних мов в умовах інтернаціоналізації освітнього простору. Визначено розширення аудиторії за рахунок активізації впровадження інформаційних технологій. Розмежовано поняття «інформаційні технології» й «інноваційні технології». Розглянуто впровадження інноваційних технологій у двох площинах: інформаційно-комунікаційній і комунікативно-діяльнісній. Наголошено на зміні ролі вчителя, який за умов інтернаціоналізації простору іншомовної освіти стає «фасилітатором комунікації у процесі спільної діяльності». В статье раскрыты особенности внедрения инновационных технологий преподавания иностранных языков в условиях интернационализации образовательного пространства. Определены возможности расширения аудитории за счет активизации внедрения информационных технологий. Разграничены понятия «информационные технологии» и «инновационные технологии». Внедрение инновационных технологий рассмотрено в двух плоскостях: информационно-коммуникационной и коммуникативно-деятельностной. Автор подчеркивает изменение роли учителя, который в условиях интернационализации пространства иноязычного образования становится «фасилитатором коммуникации в процессе общей деятельности». The article deals with the peculiarities of introducing innovation technologies in EFL teaching under the conditions of internationalization of higher education. The classroom has been presented as an open system with no walls if the rapidly developing information technologies bring the English-speaking community together. Learning has been shown as the process that starts where the students are. The author has distinguished between the terms 'information technologies' and 'innovation technologies', showing that information technologies are always seen as innovations while innovations in EFL teaching and learning cannot be limited to IT. Thus, innovations have been presented with two approaches taken into account. The first one, information communicational, deals with IT classroom applications; the second one, communicative (and task or activity based as part of it) deals with different ways used to facilitate classroom communication.  The author emphasizes the importance of changing the teacher's role to 'communication facilitator in cooperative activities' which has been enforced by the challenges of internationalization of higher education.